eHealth Systems' User Experiences from Healthcare Workers - Synnove Thomassen Andersen (Research in Social Sciences and Technology, 2019)
This article analyze how healthcare workers experience the use of eHealth systems. The empirical data is from a qualitative case study, is derived from a number of eight participating health clinics use of eHealth systems, by healthcare workers. Our analysis shows that by adopting a simple, small-scale and user-oriented approach, and by focusing on the needs and circumstances of users instead of advanced technology, it was possible to reveal domestication of eHealth systems. While these findings cannot be generalized, they provide insight into and shed light on trends concerning the negotiations of healthcare workers with eHealth technology. Themes related to the experience of user interfaces in eHealth systems have generally not been explored in detail. This research thus contributes new insight to the field.